Similarity Analysis of Alarm Sequences by a Shuffling Method - Lin, Yifan; Wang, Shengfeng; Wu, Ye; Xiao, Jinghua (Frontiers in Physics, 2021)
Modern telecommunication systems have produced many alarm messages, and alarm management is vital for telecommunication systems' high-quality performance. When considering telecommunication alarm messages over large geographical areas, direct correlating telecommunication devices should help recover the alarm messages. Because the complex correlation among telecommunication devices, most of the similarity measures encounter troubles. In this paper, we propose an index of measuring how much two-alarm series deviates from the uncorrelated situation. Synthetic sequences verify our method. Furthermore, we apply our method to analyze telecommunication devices' alarm correlation of a Chinese province. Our index for the pair similarity is capable of measuring other discrete event data.